FAKTOR - FAKTOR YANG MEMPENGARUHI MINAT PEMILIHAN KARIR MAHASISWA AKUTANSI SEBAGAI AKUNTAN PUBLIK: STUDI KASUS PADA MAHASISWA S1 JURUSAN AKUTANSI UNIVERSITAS BRAWIJAYA - Vista Rossita (Jurnal Ilmiah Mahasiswa FEB, 2018)
This study aims to determine the factors that influence the interest ofaccounting students in choosing a career as a public accountant. This study usesquantitative methods.The sample used amounted to 100 Accounting students fromthe faculties of economics and business, Universitas Brawijaya. The datacollection method used is by distributing questionnaires. The statistical test toolused to process data is Partial Least Square (PLS) analysis. The results showedthat: financial rewards, professional training, work environment, labor marketconsiderations, and personality had a positive effect on the interest of accountingstudents in choosing careers as public accountants, while professionalrecognition factors, social values and work environment did not affect studentinterest accounting in choosing a career as a public accountant.Keywords: interest, financial rewards, professional training, professional recognition,social values, work environtment, labor market consideration, personality, familyenvironment, public accountants